A systematic literature review of criteria and models for casualty distribution in trauma related mass casualty incidents. Issue 11 (November 2018) - Khajehaminian, Mohammad Reza; Ardalan, Ali; Keshtkar, Abbasali; Hosseini Boroujeni, Sayed Mohsen; Nejati, Amir; Ebadati E, Omid Mahdi Ebadati; Rahimi Foroushani, Abbas
Abstract: Introduction: Mass casualty incidents impose a large burden on the emergency medical systems, hospitals and community infrastructures. The pre-hospital and hospital capacities are usually bear the burden of casualties large numbers. One of the challenging issues in mass casualty incidents is the distribution of casualties among the suitable health care facilities. Objective: To review models and criteria affecting the distribution of casualties during the trauma-related mass causality incidents. Materials and methods: A systematic literature search in the scientific databases which included: PubMed, Scopus and Web of Science was conducted. Relevant literature which was published before August 2017 was searched. Neither the publication date nor language limitations were considered in the literature search. All the trauma-related mass casualty incidents are included in this study. Two independent reviewers conducted the data extraction and quality assessment of the documents was considered using a checklist developed by the researchers. Results: Literature search yielded 4540 documents of which 493 were duplicated and removed. After reviewing the titles and abstracts of the remaining documents (4047), only 73 documents were considered relevant. Finally, the inclusion and exclusion criteria were applied and only 30 documents were considered for data extraction and quality assessment. The study found 491 criteria to be affecting the distribution of casualties following trauma-related mass casualty incidents. These are categorized as pre-hospital (triage, treatment and transport); hospital (space, staff, stuff, system / structure); incidents' characteristics and others. The criteria which were extracted from the models are termed as "model extracted" while the other labeled as "author suggested". Conclusion: To the best of our knowledge, this is the first systematic literature review on criteria affecting distribution of casualties following trauma-related mass casualty incidents based on the pre-hospital and hospital capacities. Systematic review registration number: This review was registered in international prospective register of systematic reviews (PROSPERO) with registration number CRD42016049115.